Unlocking ginsenosides’ therapeutic power with polymer-based delivery systems: current applications and future perspectives - Yu, Xiaomin; Lu, Yun; Chen, Jiajing; Deng, Yuqian; Liu, Huan (Frontiers in Pharmacology, 2025)
Ginsenosides, as the main active ingredient of Panax plants, have been found to have extensive pharmacological activity and clinical therapeutic potential in recent years. However, its inherent physical and chemical properties such as poor solubility and low intestinal permeability result in low bioavailability, severely limiting its clinical application and translation. To address these challenges, polymeric carriers—valued for their excellent biocompatibility, structural tunability, and intelligent response functions—have been engineered to: (i) enhance solubilization via polymer conjugation and amphiphilic micellar encapsulation; (ii) achieve passive (EPR-mediated) and active (ligand-directed) tumor targeting to minimize off-target distribution; and (iii) enable on-demand drug release through pH-, ROS-, temperature-, and enzyme-responsive designs. In this review, we delve into the mechanistic principles and synergistic interactions underlying each functional module within a cohesive, function-centred design roadmap. Finally, we explore emerging interdisciplinary directions—including AI-guided polymer design, logic-gated nanocarriers, and microfluidic personalized fabrication—that promise to accelerate the bench-to-bedside translation of multifunctional ginsenoside therapeutics.